A STUDY ON SUPPLY CHAIN FRAME WORK INCONSTRUCTION INDUSTRY - Durai, Charles; Sentamilselvan, K. (International Journal of Research -GRANTHAALAYAH, 2016)
The present study made an attempt to know the significant relationship between the respondents’ demographic variables and their attitude regarding supply chain management supply chain frame work in Construction Industry. 100 samples were selected randomly from Chennai, TamilNadu. Based on the objectives certain hypotheses were formulated. Statistical tools such as one-way analysis of variance (ANOVA) and Correlation method was used to analyse the data. Questionnaire and interview method was used to collect the necessary data. Result proved that there is a significant relationship between demographic graphic variables and attitude regarding Supply chain management. Type of firm and qualification is highly significant. It is inferred that above 10 years’ experience group obtained higher mean value. So this group have favorable attitude regarding SCM.